Evaluation of Policies to Reduce Flooding Issues in the City of Palembang - Marpaung, Zailani Surya; Sobri, Kiagus Muhammad; Hendarso, Yoyok; Priatna, Satria Jaya (Universitas Pancasakti, 2025)
This article aims to evaluate the effectiveness of government policies in reducing flood risk in the city of Palembang, which is often affected by severe flooding due to low-lying geographic features and inadequate urban planning. This research uses a qualitative descriptive approach to assess the impact of current flood management strategies, focusing on structural and non-structural measures, community participation, and policy implementation. Data was collected through document analysis, interviews with key stakeholders, and direct observation in flood-prone areas. Findings show that although some structural improvements, such as improved drainage systems, have been implemented, they have not been sufficient to address recurrent flooding. Policy gaps, lack of community engagement, and poor maintenance of flood control infrastructure contribute to the city's ongoing vulnerability. This study concludes that more integrated flood management strategies, including better policy enforcement and community involvement, are needed to reduce flood risk in Palembang.